The efficacy of methotrexate in the treatment of en coup de sabre (linear morphea subtype) - Ploysyne Rattanakaemakorn (2019)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Background:En coup de sabre is a rare subtype of linear morphea, located on the forehead or frontoparietal scalp. Systemic treatment of localised morphea with methotrexate has been reported in a few clinical reports. However, there are no case series using methotrexate treatment for En coup de sabre. Objective: To evaluate the efficacy and tolerability of methotrexate in the treatment of en coup de sabre linear morphea subtype. Method: A retrospective chart review was performed for paediatric and the adult patients with en coup de sabre evaluated in the Dermatology Clinic at Wake Forest University School of Medicine treated with methotrexate. Results: There were 7 patients who met criteria for inclusion in the study. The mean age at the onset of disease was 11.8 years (ranging from 4 to 38 years). The mean duration of disease before receiving methotrexate therapy was 9.4 months (ranging from 3 to 24 months). Seven (100%) patients improved with methotrexate therapy, in an average of 2 months to disease inactivity, and 16 months to discontinuation of methotrexate. Conclusions: Methotrexate appeared to be an effective and safe therapy for en coup de sabre patients.